2007
DOI: 10.1002/cphc.200700479
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Singlet‐State Deactivation of Cyano‐Substituted Indolines in Protic Solvents via CNHO Hydrogen Bonds

Abstract: The photophysical properties of indoline (I) and three of its derivatives, namely, N-methylindoline (MI), 5-cyanoindoline (CI), and 5-cyano-N-methylindoline (CMI), are studied in H-donating solvents of varying polarity. Based on measurements of fluorescence yield and lifetime, and of triplet yield and hydrated-electron formation, two distinct mechanisms of solvent-induced fluorescence quenching are evidenced. The first mechanism involves the cyano substituent and leads to an increase in the rate constant of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…36 Actually, uorescence quenching by protic solvents has been reported for several organic dyes but the exact mechanism has not been fully elucidated. [43][44][45][46][47][48][49][50][51][52] One common factor in all cases is the presence of strong hydrogen bonds between the solute and the protic solvent. Moreover, the HB strength in most cases increases signicantly in the excited state as a result of intramolecular charge-transfer (CT) type excitation.…”
Section: Global Target Analysis Based On the Eigen-weller Modelmentioning
confidence: 99%
“…36 Actually, uorescence quenching by protic solvents has been reported for several organic dyes but the exact mechanism has not been fully elucidated. [43][44][45][46][47][48][49][50][51][52] One common factor in all cases is the presence of strong hydrogen bonds between the solute and the protic solvent. Moreover, the HB strength in most cases increases signicantly in the excited state as a result of intramolecular charge-transfer (CT) type excitation.…”
Section: Global Target Analysis Based On the Eigen-weller Modelmentioning
confidence: 99%
“…Hydrogen bonding often affects the photodynamic properties of aromatic molecules as well as their static spectral properties. In particular, in aromatic carbonyl compounds, [1][2][3][4][5][6][7][8][9] nitrogen-containing heterocyclic compounds 10 and aromatic amines, [11][12][13] the rates of radiationless transitions (internal conversion and intersystem crossing) are remarkably affected by intramolecular and intermolecular hydrogen-bonding interactions on the carbonyl oxygen, nitrogen hetero-atom, or amino groups. We have demonstrated that aniline derivatives with an electron-withdrawing group at the ortho-or meta-position exhibit rapid internal conversion through intermolecular hydrogen-bonding interactions with protic solvent molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Az 5-ciano-N-metilindolin esetében igazoltuk, hogy a cianocsoport és a protikus oldószerek között hidrogénkötés alakul ki, amely gerjesztett állapotban is stabil. 23 A jelenség kioltást okoz, ami a lokális víztartalom fluoreszcenciás kimutatására ad lehetõséget. A níluskék, az oxazin 720 és a kumarin 102 esetében a sav-bázis tulajdonságok változását vizsgáltuk gerjesztett állapotban.…”
Section: Lágy Anyagok Kutatócsoportunclassified